The Use Traditional Game Cublak-Cublak Suweng to Improve Arabic Vocabulary Achievements - Novia Indah Kurniawati; Lailatul Qomariyah; Mustafa Farouq Abdul-Aaleem Mahmoud (UIN ANTASARI, 2022)
The research purpose is to know Arabic vocabulary acquisition on students by traditional game cublak-cublak suweng (CSS). The applied approach in this research is PTK (class based research) held in cycles. Each cycle composed two meetings. The first meeting is used to give the material, drill vocabularies, and give test paper connected with fresh taught vocabularies. Second meeting is used to review taught vocabularies in first meeting by traditional game CSS. The data collection is by using interview, observation, giving tests, and documentation. The result of research indicates using game method, especially in traditional game cublak-cublak suweng increase students' Arabic vocabulary acquisition. The indicator is increasing grades degree from first cycle to other cycles; lack in first cycle, sufficient in second cycle, and good in third cycle.